2021
DOI: 10.1016/j.ibneur.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical nerve stimulation in the management of calf muscle spasticity in cerebral palsy: A pilot study

Abstract: This study sets out to evaluate the effectiveness of transcutaneous electrical nerve stimulation (TENS) in the management of calf muscle spasticity in children with cerebral palsy. The study follows a one group pre-test–post-test design involving fifteen children with spastic cerebral palsy, presenting with calf muscle spasticity. Spasticity was assessed before and after a 30 min application of TENS to the bilateral calf muscles. The H-reflex (electromyography) of the calf muscles and Modified Ashworth Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is in line with the study by Logosu et al in 15 children with spastic CP aged between 1 and 10 years who were given 100 Hz electrical stimulation (TENS) therapy for 30 minutes on the ankle dorsiflexion muscle which resulted in a significant decrease in MAS and an increase in range of motion (p = 0.038). TENS can reduce spasticity in CP by reducing neuronal excitability 30 and decreasing stretch reflex sensitivity 31 . A significant increase in muscle activity at rest in individuals with spastic CP indicates the occurrence of hypertonia 29,32 .…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the study by Logosu et al in 15 children with spastic CP aged between 1 and 10 years who were given 100 Hz electrical stimulation (TENS) therapy for 30 minutes on the ankle dorsiflexion muscle which resulted in a significant decrease in MAS and an increase in range of motion (p = 0.038). TENS can reduce spasticity in CP by reducing neuronal excitability 30 and decreasing stretch reflex sensitivity 31 . A significant increase in muscle activity at rest in individuals with spastic CP indicates the occurrence of hypertonia 29,32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the treatment of peripheral nervous system diseases, direct TENS has found application in the management of patients with brain and spinal cord disorders. It is suggested that the pathogenetic basis of the central antispastic effect of TENS is a decrease in neuronal excitability, a decrease in the sensitivity of the stretch reflex [ 27 , 28 ] and an increase in presynaptic inhibition [ 29 ]. Clinically, in patients with central paralysis, direct TENS was reported to be effective in the regression of motor deficit of ankle dorsiflexion after direct stimulation of the common peroneal nerve [ 30 ] and in the recovery of motor function of the hand after direct stimulation of the median nerve [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS), the application of surface electrodes on affected muscles, decreases neuron excitability and is also used to decrease spasticity in CP [10,23,24]. TENS increases PROM [23] and improves localized oxygenation [25] and muscle blood research demonstrates that patients with spastic CP benefit from TENS to our knowledge, only one study combined DN with surface electrode electrical stimulation (ES) to treat a stroke patient [23].…”
Section: Introductionmentioning
confidence: 99%